Indications for and Findings on Transthoracic Echocardiography in COVID-19 - Jain, Sneha S. (J Am Soc Echocardiogr, 2020)
BACKGROUND: Despite growing evidence of cardiovascular complications associated with coronavirus disease 2019 (COVID-19), there are few data regarding the performance of transthoracic echocardiography (TTE) and the spectrum of echocardiographic findings in this disease. METHODS: A retrospective analysis was performed among adult patients admitted to a quaternary care center in New York City between March 1 and April 3, 2020. Patients were included if they underwent TTE during the hospitalization after a known positive diagnosis for COVID-19. Demographic and clinical data were obtained using chart abstraction from the electronic medical record. RESULTS: Of 749 patients, 72 (9.6%) underwent TTE following positive results on severe acute respiratory syndrome coronavirus-2 polymerase chain reaction testing. The most common clinical indications for TTE were concern for a major acute cardiovascular event (45.8%) and hemodynamic instability (29.2%). Although most patients had preserved biventricular function, 34.7% were found to have left ventricular ejection fractions ≤ 50%, and 13.9% had at least moderately reduced right ventricular function. Four patients had wall motion abnormalities suggestive of stress-induced cardiomyopathy. Using Spearman rank correlation, there was an inverse relationship between high-sensitivity troponin T and left ventricular ejection fraction (ρ = −0.34, P = .006). Among 20 patients with prior echocardiograms, only two (10%) had new reductions in LVEF of >10%. Clinical management was changed in eight individuals (24.2%) in whom TTE was ordered for concern for acute major cardiovascular events and three (14.3%) in whom TTE was ordered for hemodynamic evaluation. CONCLUSIONS: This study describes the clinical indications for use and diagnostic performance of TTE, as well as findings seen on TTE, in hospitalized patients with COVID-19. In appropriately selected patients, TTE can be an invaluable tool for guiding COVID-19 clinical management.